2021
DOI: 10.1002/agg2.20209
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and environmental performance of biochar amendment in alluvial soils under subtropical sugarcane production

Abstract: This study investigated the amendment of sugarcane bagasse biochar (SCBB) on soil fertility, crop yield, and nutrient loss in two different-textured soils under sugarcane (Saccharum spp.) production. Eleven megagrams per hectare of freshly incorporated biochar increased yield of plant cane by 22% in light-texture soil (LS) and 12% in heavy-textured soil (HS). Although the overall yield of the ratoon crop was lower, the biochar treatment produced 20 and 14% higher yields than the control at the LS and HS sites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…Chen et al [31] reported that biochar application reduced soil dry density and increased available moisture, resulting in higher yield and sugar content. Similarly, Tafti revealed that, by applying biochar, crop yield increased in both light-and heavy-texture soil and reduced nutrient losses in subtropical sugarcane production [49]. Under saline stress conditions, Farhangi-Abriz and Torabian [50] also indicated that biochar modifies the oxidative stress in plant tissues of bean seedlings and thereby enhances plant growth.…”
Section: Discussionmentioning
confidence: 94%
“…Chen et al [31] reported that biochar application reduced soil dry density and increased available moisture, resulting in higher yield and sugar content. Similarly, Tafti revealed that, by applying biochar, crop yield increased in both light-and heavy-texture soil and reduced nutrient losses in subtropical sugarcane production [49]. Under saline stress conditions, Farhangi-Abriz and Torabian [50] also indicated that biochar modifies the oxidative stress in plant tissues of bean seedlings and thereby enhances plant growth.…”
Section: Discussionmentioning
confidence: 94%
“…Both samples presented average elemental percentages of 69.4 wt % of C, 2.9 wt % of H, 0.88 wt % of N, and 16.8 wt % of O. From the implementation of a thermal conversion process of SCB in sugarcane industries, the produced biochar can be destined to soil applications, thus improving the production capacity of sugarcane, as well as in applications for energy generation for industry [32,33]. On the basis of the observation that the gases and LLFs were the only ones influenced by the processes, to evaluate the effect of the atmosphere alteration and catalyst insertion over the chemical composition of these products, we conducted analyses for chemical characterization.…”
Section: Influence Of the Processes On Product Distribution And Eleme...mentioning
confidence: 99%